In situ video monitoring of by-catch interactions within commercial rock lobster (Jasus edwardsii) fishing traps. Issue 1 (2nd January 2018) - Asanopoulos, Christina H.; Linnane, Adrian J.; Hoare, Matthew; Huveneers, Charlie
ABSTRACT: The incidental capture of non-target and undersized target species during commercial fishing operations has been identified as a major issue and ongoing challenge for fisheries management. In the Northern Zone rock lobster ( Jasus edwardsii ) fishery (NZRLF) of South Australia, escape gaps have been mandatory in all commercial fishing traps since 2002 to reduce non-target species (by-catch) catch rates and juvenile lobster mortality. This study used in situ video monitoring of by-catch species in traps with and without escape gaps to understand how by-catch species interact within commercial fishing traps. Twenty-two different by-catch species were observed entering commercial rock lobster traps, 20 of which were temperate reef finfish. Overall, on-board by-catch rates were significantly higher in hauled traps without escape gaps and were dominated by reef-dwelling finfish species, particularly Meuschenia hippocrepis and Notolabrus tetricus . However, in situ video monitoring within traps showed no difference in the maximum number of finfish by-catch (MaxN) in traps with or without escape gaps. We suggest that the difference in by-catch rates between hauled traps with and without escape gaps may be driven by species-specific behavioural interactions within traps prior to hauling. Overall, this study shows that the implementation of escape gaps in the NZRLF has considerably reduced fishery by-catch rates. Furthermore, the use of in situ video monitoring has provided a better understanding of by-catch behavioural interactions within traps, not previously identified in on-board sampling research, which may partly explain the mechanisms underpinning escape gap effectiveness.